PENGARUH KAPASITAS SUMBER DAYA MANUSIA DAN SIPD TERHADAP PENGELOLAAN KEUANGAN - Muji Cahyo Wijaya; Ati Retna Sari; Mochamad Fariz Irianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
Quality financial management in local governments requires competent human resources and integrated information systems. This study aims to examine the influence of human resource (HR) capacity and the use of the Regional Government Information System (SIPD) on financial management performance. A quantitative approach was employed through a survey of 35 staff members involved in financial operations at the General Affairs Division of the Regional Secretariat of Malang Regency. The results of the study indicate that both Human Resources (HR) and the utilization of the Regional Government Information System (SIPD) have a positive and significant effect on financial management, with coefficient values of 0.617 (sig. 0.000) and 0.242 (sig. 0.045), respectively. These findings highlight the importance of enhancing employee competencies and optimizing information technology utilization to improve the effectiveness and accountability of regional financial management.